2015
DOI: 10.3390/ijms16023350
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols in Prevention and Treatment of Prostate Cancer

Abstract: Prostate cancer is the most prevalent disease affecting males in many Western countries, with an estimated 29,480 deaths in 2014 in the US alone. Incidence rates for prostate cancer deaths have been decreasing since the early 1990s in men of all races/ethnicities, though they remain about 60% higher in African Americans than in any other group. The relationship between dietary polyphenols and the prevention of prostate cancer has been examined previously. Although results are sometimes inconsistent and variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
170
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(175 citation statements)
references
References 165 publications
2
170
0
3
Order By: Relevance
“…In the year 2014, 220,800 new PCa cases were diagnosed in United States and 29,480 PCa patients died of the disease [1]. PCa usually begins with androgen-dependent growth with positive androgen receptor (AR+) expression, showing sensitive to androgen deprivation therapy (ADT) [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…In the year 2014, 220,800 new PCa cases were diagnosed in United States and 29,480 PCa patients died of the disease [1]. PCa usually begins with androgen-dependent growth with positive androgen receptor (AR+) expression, showing sensitive to androgen deprivation therapy (ADT) [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…This is largely due to epidemiological studies connecting consumption of certain foods with reduced cancer incidence. In context of prostate cancer, dietary polyphenols have been proposed as promising candidates for future clinical management (3). These non-toxic, well-tolerated compounds are key modulators of several signaling pathways (4) and a renewed interest in them can be attributed to their activity against stem cells, microRNAs as well as the epigenetic changes (3; 5).…”
Section: Introductionmentioning
confidence: 99%
“…In context of prostate cancer, dietary polyphenols have been proposed as promising candidates for future clinical management (3). These non-toxic, well-tolerated compounds are key modulators of several signaling pathways (4) and a renewed interest in them can be attributed to their activity against stem cells, microRNAs as well as the epigenetic changes (3; 5). Epidemiological studies have also suggested a decreased risk of cancer in populations with high olive intake (6) and there has been an interest in evaluating traditional Mediterranean diet, with abundance of olive oil consumption, for possible reduced prostate cancer risk (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that natural polyphenol compounds have a great effect on cancer protection (Howe et al., 1992). These compounds that are secondary metabolites in plants and polyphenol diet have shown promising against cancer (Lall, Syed, Adhami, Khan, & Mukhtar, 2015). RSV as a polyphenolic compound in plants has a broad protective activity against several types of cancer.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%